2019
DOI: 10.1101/647651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecological and genomic attributes of novel bacterial taxa that thrive in subsurface soil horizons

Abstract: While most bacterial and archaeal taxa living in surface soils remain undescribed, 5this problem is exacerbated in deeper soils owing to the unique oligotrophic conditions found in the subsurface.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 62 publications
(61 reference statements)
1
16
0
Order By: Relevance
“…Here, our data of 16S rRNA gene sequences showed that Anaerolinea steadily increased from 0.001% in the surface organic layer to 0.009% in the middle organic layer, 0.011% in the deep organic layer, and 1.162% in the mineral layer, despite the insignificant difference between warmed and control plots in this study. Interestingly, the phylum Dormibacteraeota , which has no cultured representatives so far (Brewer et al, 2019), was abundant in subsurface soils. As Dormibacteraeota appears to adapt to cold and C‐depleted environments (Costello, 2007), it might be used as a bioindicator of cold soils because it is highly abundant in much permafrost of Alaska (Tas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Here, our data of 16S rRNA gene sequences showed that Anaerolinea steadily increased from 0.001% in the surface organic layer to 0.009% in the middle organic layer, 0.011% in the deep organic layer, and 1.162% in the mineral layer, despite the insignificant difference between warmed and control plots in this study. Interestingly, the phylum Dormibacteraeota , which has no cultured representatives so far (Brewer et al, 2019), was abundant in subsurface soils. As Dormibacteraeota appears to adapt to cold and C‐depleted environments (Costello, 2007), it might be used as a bioindicator of cold soils because it is highly abundant in much permafrost of Alaska (Tas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ca . Dormibacterota have been reported to be more abundant in low carbon (Brewer et al ., 2019), or low nitrogen environments (Tas et al ., 2014), with an increase in abundance with depth of sampling reported (Tas et al ., 2014; Woodcroft et al ., 2018; Brewer et al ., 2019). For example, Ca .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ca . Dormibacterota have been shown to increase 27‐fold in relative abundance at a sampling depth of 90 cm in sub‐surface soil horizons in North American forest soils, representing up to 60% relative abundance in these nutrient‐depleted soils (Brewer et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Soil pH may also increase with depth in instances where the parent material is enriched in base cations (Brubaker et al 1993). These gradients in soil properties result in subsoil microbial communities that are vastly different than their surface soil counterparts (Eilers et al 2012;Brewer et al 2019). Soil pH (Sinsabaugh et al 2008;Kivlin & Treseder 2014), substrate availability and demand (Olander & Vitousek 2000;Doveet al 2019), and microbial community composition (Schneckeret al 2015) influence EE activities in surface soils.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is currently unknown if these controls in surface soils extend into the subsoil. We posit that EE activities at depth may follow different patterns than in the surface horizons given that EEs at depth are less responsive to environmental perturbations (Jing et al 2017), subsoils have greater heterogeneity of organic substrates than at the surface (Salomé et al 2010), and the microbial communities at depth are dominated by oligotrophic microorganisms (Brewer et al 2019).…”
Section: Introductionmentioning
confidence: 99%